The Key to Communication Skills in the Patient-Physician Relationship - Yousuf, Rabeya; Alsharkawy, Alsyed; Salam, Md Mushtahid; Akter, Shaima; Pasha, Mehbub Alam; Begum, Hamida; Salam, Abdus (International Journal of Human and Health Sciences (IJHHS), 2024)
Abstract not available International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 305-309